KARAKTERISTIK PETANI PADI PESERTA PROGRAM UPAYA KHUSUS PADI JAGUNG KEDELAI (UPSUS PAJALE)DI DESA BUNGA RAYA KECAMATAN BUNGA RAYA KABUPATEN SIAK - Marnala, Juvan; Yulida, Roza; Sayama, Eri (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
This research is intended to understand the characteristic of the farmers, stage on the Specially Efforts Corn, Soybean, Paddy(UPSUS PAJALE) at Bunga Raya village. This research was conducted at Bunga Raya village that is located in the Siak Regency. Multi stage sampling was used as the method to choose locations. The samples were gathered using Purposive Sampling method. This research uses 48 farmers data as samples. Data analysis which is used for this research is the descriptive method. The goals were analyzed using Likert Scale. The results of this research shows us the paddy farmers’ internal characteristics at Bunga Raya village such as: the farmers’ productive ages are within the range of 40-46 years, most of the farmers’ are High School graduates, each farmers’ family consists of 4-5 persons, farmers’ experiences are between 17-23 years, the land area that the farmers manage is between 0,5-1ha and the farmers are highly cosmopolitans. The external characteristics of farmers are medium when are evaluated according to the instructors’ intensity, the accuracy of instructors channel, the amount of information sources, the affordability of production facilities price and the availability of production facilities.Keywords:Internal Characteristics, External Characteristics,Specially Efforts Paddy, Corn, Soybean, (UPSUS PAJALE)